Evaluation of Islamic Religious Education Learning on SKI Material: Development of HOTS Instrument in Senior High School - Bayu Lesmana; Risnita Risnita; Dedi Sastradika; Sri Ramdayeni Sakunti (IJECA (International Journal of Education and Curriculum Application), 2026)
Learning of Islamic Religious Education (PAI) on the subject of Islamic Cultural History (SKI) is still dominated by conventional methods and evaluation that has not been oriented toward Higher Order Thinking Skills (HOTS), resulting in students’ critical thinking skills not developing optimally. This study aims to develop and validate a Higher Order Thinking Skills (HOTS)-based assessment instrument for the Islamic Cultural History (SKI) subject at the eleventh-grade level of senior high school. The research employed a Research and Development (R&D) approach using a modified 4D model consisting of define, design, and develop stages. The instrument comprised 30 multiple-choice items measuring cognitive levels C4, C5, and C6 based on the revised Bloom’s taxonomy. Content validity was analyzed using Aiken’s V, while reliability, item difficulty, and discrimination were examined using the Rasch model through QUEST program software. The results showed a very high content validity index (Aiken’s V = 0.88) and excellent reliability (0.91). Rasch analysis indicated that most items fit the model (INFIT MNSQ 0.77–1.33), with a balanced distribution of item difficulty and very good discrimination indices. Three items were identified as misfit and subsequently revised to maintain the composition of 30 HOTS-based items. This study contributes to the development of a psychometrically tested HOTS assessment instrument for Islamic Religious Education, integrating Rasch modeling to ensure objectivity and measurement precision. The instrument provides a more robust and theoretically grounded evaluation tool compared to previous studies that relied on classical test analysis or did not fully integrate HOTS constructs.